2021
DOI: 10.1111/pde.14665
|View full text |Cite
|
Sign up to set email alerts
|

Access as equity: Addressing the distribution of the pediatric dermatology workforce

Abstract: Equitable distribution of the physician workforce is critical to ensuring the health of the world's population. Significant imbalances in this distribution can compromise access to care and have lasting implications on health outcomes. 1 Advancements in healthcare delivery and expanded health coverage have accelerated the race to health equity over the past three decades; however, the pace of progress remains uneven, both between and within countries.National health averages conceal the fact that some gains ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several studies have shown that physicians typically practice in regions where physician supply is already high, leaving underserved areas vulnerable to difficulties in access. 4 The Walsh et al study confirms that pediatric ophthalmologists also concentrate in populated areas. However, while the authors suggest a notion of incentivizing the redistribution of the existing pool of pediatric ophthalmologists to more underserved areas, the more significant problem appears to be the astonishing scarcity of total pediatric ophthalmologists.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies have shown that physicians typically practice in regions where physician supply is already high, leaving underserved areas vulnerable to difficulties in access. 4 The Walsh et al study confirms that pediatric ophthalmologists also concentrate in populated areas. However, while the authors suggest a notion of incentivizing the redistribution of the existing pool of pediatric ophthalmologists to more underserved areas, the more significant problem appears to be the astonishing scarcity of total pediatric ophthalmologists.…”
mentioning
confidence: 88%
“…Next, it is a seller’s market, where pediatric ophthalmologists ultimately have a high degree of flexibility in selecting the location of their practice given the small number of eye care professionals. Several studies have shown that physicians typically practice in regions where physician supply is already high, leaving underserved areas vulnerable to difficulties in access . The Walsh et al study confirms that pediatric ophthalmologists also concentrate in populated areas.…”
mentioning
confidence: 99%
“…There are 4.3 pediatric dermatologists per 1 000 000 children nationally [10 ▪ ]; this ratio is ten times lower than adult dermatologists [11]. There is a markedly uneven distribution of pediatric dermatologists between urban and rural counties [8 ▪ –10 ▪ ,12,13]. According to a 2020 study, 98% of all pediatric dermatologists practice in a metropolitan county, none practice in rural counties [10 ▪ ], and seven states are without a pediatric dermatologist [8 ▪ ].…”
Section: Barriersmentioning
confidence: 99%
“…Early exposure and familiarity with target communities are strongly associated with physician recruitment and retention [9 ▪ ]. Patients of minority races and gender identities have less access to dermatologic care; diversifying the dermatology workforce and educational curriculum is critical to address this.…”
Section: Looking Forwardmentioning
confidence: 99%
See 1 more Smart Citation